Collaborative Governance in Corporate Social Responsibility Forum in Banyumas Regency - Furqoni, Iqtikaful; Rosyadi, Slamet; Isna, Alizar (Jurnal Bina Praja, 2019)
This research is motivated by the SATRIA CSR (Corporate Social Responsibility) Forum in Banyumas Regency which involves various parties such as local governments, companies, academics, NGOs, and mass media that collaborate in supporting regional development through CSR. Therefore, this paper aims to describe in-depth the governance of the SATRIA CSR Forum in Banyumas Regency in the perspective of collaborative governance. This research uses a qualitative method with a phenomenological approach. The research location was in Banyumas Regency, with the target of the research consisting of government elements, private elements, mass media elements, NGOs, the community, and academics. The selection of informants was carried out using purposive sampling and snowball sampling techniques. The data analysis method used is the interactive analysis. The results found that the existence of internal and external dialogue was good initial progress in the governance of the SATRIA CSR Forum. Even so, there are still some aspects of CSR Forum governance that have not been maximized, such as stakeholder's commitment and the business community's understanding of CSR regulations. Therefore, efforts are needed to get the business community involved in the SATRIA CSR Forum. In this case, the role of local government is one of the keys for the business world to be involved, including by providing understanding to the business community regarding CSR regulations. The results of this study contribute to an understanding of the implementation of collaborative approaches in the context of CSR programs at the local level.